Dissimilarity effects on house prices: what is the value of similar neighbours? - Said Benjamin Bonakdar; Michael Roos (Journal of Economic Interaction and Coordination, 2022)
Residential choice does not only depend on properties of the dwelling, neighbourhood amenities and affordability, but is also affected by the population composition within a neighbourhood. All these attributes are capitalised in the house price. Empirically, it is not easy to disentangle the effect of the neighbourhood on house prices from the effects of the dwelling attributes. We implement an agent-based model of an urban housing market that allows us to analyse the interaction between residential choice, population composition in a neighbourhood and house prices. Agents differ in terms of education, income and group affiliation (majority vs. minority). Whereas rich agents can afford to move to preferred places, roughly 13.01% of poor minorities and 8.02% of poor majority agents are locked in their current neighbourhood. We show that a preference to live among similar neighbours has a strong competitive effect on rich households and drives up their house prices. This is not the case with a preference for status. By introducing a policy that provides agents more access to credit, we find that all population groups denote higher satisfaction levels. Poor agents show the largest improvements. The general satisfaction level across all population groups increases. However, the extra credit accessibility also drives up house prices and leads to higher wealth inequality within the city. If agents have a preference for status rather than for similarity, the effect of the overall inequality is smaller, since agents become more satisfied living in areas with less similar agents.
Keywords: C63; R21; R23; R32; 330; Agent-based modelling; Residential choice; Housing demand; Neighbourhood characteristics; House prices